STRATEGIES AND OPERATION PRINCIPLES OF LOGISTIC INFORMATION SYSTEMS - Smagulova, A.; Tentekbayeva, Zh.; Abdin, A. (Scientific Journal of Astana IT University, 2020)
Over the last few years the so-called new logistic technologies are rapidly developed. Information systems hold the central position in these technologies. Development of logistics in the developed countries not least are stimulated with the need of fast reaction of producers to market condition, aspiration to adapt in the changing situations in short time. The central idea of logistics is planning, management and control of entrepreneurial activity, all material and information flows connected with this activity. Information systems in logistics assume fast appropriate response to the market demand, tracking delivery time, optimization of functions in chains of delivery and supply. The research of modern backbone of information technologies in logistics is conducted in this article. Modern information technologies in logistics are analyzed. Modern technologies of information data processing in logistic streams and creation of logistic information technologies are also considered in the article. Some types of information technologies in logistics, structural principles and principles of operation of logistic information systems and also problems in the process of creation of logistic information technologies are described. The article is addressed to a wide range of researchers and experts in the field of logistics and information technologies